2023
DOI: 10.57135/jier.1229524
|View full text |Cite
|
Sign up to set email alerts
|

Uzman Öğretmenlik Yetiştirme Programının Öğretmenlik Mesleği Genel Yeterlilikleri Çerçevesinde Değerlendirilmesi

Abstract: Eğitim bireyde kalıcı izli davranış değişikliği oluşturma süreci olarak adlandırılırken eğitimin en önemli iki ögesinden biri öğretmendir. Öğretmenin en temel görevlerinin içerisinde yaşadığı toplumu bütünleştirmesi ve çağın gereksinimleri doğrultusunda toplumu şekillendirmesi bulunmaktadır. Öğretmenlik mesleği toplumsal bütünleşme, değişim ve gelişimi sağlaması bakımından diğer meslek gruplarından ayrılmaktadır. Bireylerin bu mesleği yerine getirebilmesi için öğretmenliğe özgü nitelik ve yeterliliklere sahip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…While most of the teachers stated that ETTPS did not meet their expectations, a few teachers stated that it met their expectations partially. These results are supported by the research results of Avcı and Kayıran (2023). Similarly, Baş, Kibar Furtun, Kapusızoğlu, and Ulu Aslan (2023) found in their research that the expert teacher exam did not meet teachers' expectations.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…While most of the teachers stated that ETTPS did not meet their expectations, a few teachers stated that it met their expectations partially. These results are supported by the research results of Avcı and Kayıran (2023). Similarly, Baş, Kibar Furtun, Kapusızoğlu, and Ulu Aslan (2023) found in their research that the expert teacher exam did not meet teachers' expectations.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
“…A great majority of teachers agreed that the training does not contribute to professional development. In parallel with these results, in the research conducted by Avcı and Kayıran (2023), it was firmly concluded that the expert teacher training program did not contribute to the general qualifications of the teaching profession. An expert education model should be used in teachers' career progression and professional development (Şendağ & Gedik, 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Sınıf öğretmenlerinin ÖMK ile ilgili görüşlerinin belirlenmesi (Bakırcı ve diğ., 2023), öğretmenlik mesleği genel yeterlikleri çerçevesinde uzman öğretmenlik yetiştirme programının değerlendirilmesi (Avcı & Kayıran, 2023), ÖMK'ye ilişkin okul yöneticisi ve öğretmen görüşlerinin incelenmesi (Genç & Balyer, 2023), ÖMK hakkında öğretmen görüşlerinin belirlenmesi (Gül & Güngör, 2022), farklı disiplinlerde görev yapan (Miles & Huberman, 1994). Bu analiz sonucunda ortaya çıkan tema, kategori ve kodlar tablolar halinde verilmiştir.…”
Section: Introductionunclassified